Splitting of PG(1,27) by Sets, Orbits, and Arcs on the Conic - Abdulkareem, Emad Bakr (Iraqi Journal of Science, 2021)
This research aims to give a splitting structure of the projective line over the finite field of order twenty-seven that can be found depending on the factors of the line order. Also, the line was partitioned by orbits using the companion matrix. Finally, we showed the number of projectively inequivalent -arcs on the conic through the standard frame of the plane PG(1,27)